Point-of-care HPV DNA testing of self-collected specimens and same-day thermal ablation for the early detection and treatment of cervical pre-cancer in women in Papua New Guinea: a prospective, single-arm intervention trial (HPV-STAT). Issue 9 (September 2022) - Vallely, Andrew J B; Saville, Marion; Badman, Steven G; Gabuzzi, Josephine; Bolnga, John; Mola, Glen D L; Kuk, Joseph; Wai, Malts; Munnull, Gloria; Garland, Suzanne M; Brotherton, Julia M L; Kelly-Hanku, Angela; et al.
Summary: Background: WHO recommends human papillomavirus (HPV) testing and same-day treatment for cervical screening in low-income and middle-income countries (LMICs); however, few published data exist on the validity of the strategy. We aimed to evaluate the clinical performance, treatment completion rates, adverse events profile, and acceptability of a fully integrated strategy, comprising point-of-care HPV DNA testing of self-collected specimens and same-day thermal ablation, for screening of cervical cancer in women in Papua New Guinea. Methods: HPV-STAT was a large-scale, prospective, single-arm intervention trial conducted at two clinical sites in Papua New Guinea. Cervical screening clinics with an on-site consultant gynaecologist were selected in consultation with national and provincial health authorities, church health services, and local stakeholders. Eligible participants were women aged 30–59 years attending cervical screening services at the two clinics, who were willing to comply with study procedures and able to provide written informed consent. Women self-collected vaginal specimens for point-of-care GeneXpert testing (Cepheid, Sunnyvale, CA, USA) for oncogenic HPV types. Women testing positive for HPV underwent pelvic examination followed by same-day thermal ablation or referral for gynaecology review. All HPV-positive women and a 15% random sample of HPV-negative women provided a clinician-collected cervical specimen for liquid-based cytology. The primary outcome was clinical performance (ie, sensitivity, specificity, positive predictive value [PPV], and negative predictive value [NPV]) of the strategy for the detection of high-grade squamous intraepithelial lesion (HSIL) or worse. This trial is registered with ISRCTN, ISRCTN13476702. Findings: Between June 5, 2018, and Jan 6, 2020, we recruited 4285 women, 3638 (84·9%) of whom tested negative for HPV and 647 (15·1%) tested positive for one or more oncogenic HPV type. Sensitivity of the algorithm to detect HSIL or worse was 85·4% (95% CI 81·0–89·6), with specificity 89·6% (88·6–90·6), PPV 35·2% (31·6–39·0), and NPV 98·9% (98·6–99·2). Among HPV-positive women, 602 (93·0%) received same-day thermal ablation and 42 (6·5%) were referred for gynaecology review, 37 (88·1%) of whom attended. Acceptability was high among both HPV-positive and HPV-negative women. Among the 329 HPV-positive women who attended a 3-month follow-up visit, 51 (15·5%) reported mild adverse symptoms that resolved in all cases by the follow-up visit. There were no serious adverse events. Interpretation: We conducted the first real-world evaluation of a fully integrated point-of-care HPV self-collect, test, and treat strategy for same-day cervical screening in a LMIC and found it to be effective, acceptable, and safe when implemented at scale in primary health-care facilities in Papua New Guinea. Our findings support the introduction and scale-up of HPV screening and treatment for the control and elimination of cervical cancer in LMICs, as recommended by WHO. Funding: Australian National Health and Medical Research Council.